2022
DOI: 10.3390/electronics11121810
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cascade Model for End-to-End Aspect-Based Social Comment Sentiment Analysis

Abstract: The end-to-end aspect-based social comment sentiment analysis (E2E-ABSA) task aims to discover human’s fine-grained sentimental polarity, which can be refined to determine the attitude in response to an object revealed in a social user’s textual description. The E2E-ABSA problem includes two sub-tasks, i.e., opinion target extraction and target sentiment identification. However, most previous methods always tend to model these two tasks independently, which inevitably hinders the overall practical performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Additionally, the work involved in ASC relies on the aspect term as a pre-identified feature of the model in conjunction with the input sentence, which is not the case in real-world scenarios. To overcome these limitations, various studies on English ABSA have developed models that can perform these subtasks jointly, either through a hierarchical approach [34] or an End-to-End approach [17,35,36,15]. The following studies correspond to the English E2E-ABSA.…”
Section: B End-to-end Aspect-based Sentiment Analysis (E2e-absa)mentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the work involved in ASC relies on the aspect term as a pre-identified feature of the model in conjunction with the input sentence, which is not the case in real-world scenarios. To overcome these limitations, various studies on English ABSA have developed models that can perform these subtasks jointly, either through a hierarchical approach [34] or an End-to-End approach [17,35,36,15]. The following studies correspond to the English E2E-ABSA.…”
Section: B End-to-end Aspect-based Sentiment Analysis (E2e-absa)mentioning
confidence: 99%
“…The GloVe [37] embeddings and targetposition information are used as features. In [17], the authors propose a CasNSA model that consists of several modules: a contextual semantic representation module, a target boundary recognizer, and a sentiment polarity identifier. The model was tested on four different datasets, and the highest F1-score achieved was on the SemEval-2014 dataset.…”
Section: B End-to-end Aspect-based Sentiment Analysis (E2e-absa)mentioning
confidence: 99%
See 2 more Smart Citations
“…An ABSA framework based on a recurrent neural network is tested in [24]; the authors showed that their framework provides better accuracy than other ABSA methods. In [25], a cascade-target-oriented neural ABSA model is applied in multi-label classifications of user reviews extracted from tweets. The limitation of neural-based ABSA methods is domain dependency; as consumers' comments are strongly linked to productservice, the application of these methods to different domains does not guarantee the same performance.…”
Section: Related Workmentioning
confidence: 99%